Field–Frequency-Dependent Non-linear Rheological Behavior of Magnetorheological Grease Under Large Amplitude Oscillatory Shear - Wang, Huixing; Chang, Tianxiao; Li, Yancheng; Li, Shaoqi; Zhang, Guang; Wang, Jiong (Frontiers in Materials, 2021)
This article investigates the influence of frequency on the field-dependent non-linear rheology of magnetorheological (MR) grease under large amplitude oscillatory shear (LAOS). First, the LAOS tests with different driving frequencies were conducted on MR grease at four magnetic fields, and the storage and loss moduli under the frequency of 0.1, 0.5, 1, and 5 Hz were compared to obtain an overall understanding of the frequency-dependent viscoelastic behavior of MR grease. Based on this, the three-dimensional (3D) Lissajous curves and decomposed stress curves under two typical frequencies were depicted to provide the non-linear elastic and viscous behavior. Finally, the elastic and viscous measures containing higher harmonics from Fourier transform (FT)-Chebyshev analysis were used to quantitatively interpret the influence of the frequency on the non-linear rheology of MR grease, namely, strain stiffening (softening) and shear thickening (thinning), under LAOS with different magnetic fields. It was found that, under the application of the magnetic field, the onset of the non-linear behavior of MR grease was frequency-dependent. However, when the shear strain amplitude increased in the post-yield region, the non-linear rheology of MRG-70 was not affected by the oscillatory frequency.